2017
DOI: 10.15835/nsb9110022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Foliar and Petiole Anatomy of Some Members of the Genus Dieffenbachia Schott in the Family Araceae

Abstract: This study provides detailed information of the anatomical attributes of the epidermis and the three regions of the petiole of four members of the genus Dieffenbachia Schott. Fresh samples of the leaves of Dieffenbachia picta Schott, Dieffenbachia oerstedii Schott, Dieffenbachia senguine (Jacq) Schott and Dieffenbachia senguine cultivar 'Candida' Schott were used. Epidermal peels and transverse sections were made following standard procedures. Generic characters revealed uniform epidermal cell shape on the aba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
2
8
1
Order By: Relevance
“…We found that when a difference in cell solidity was present, the abaxial cells tended to have more undulations (lower solidity, Fig. a), in line with the qualitative literature (Linsbauer, ; Watson, ; Arogundade & Adedeji, ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We found that when a difference in cell solidity was present, the abaxial cells tended to have more undulations (lower solidity, Fig. a), in line with the qualitative literature (Linsbauer, ; Watson, ; Arogundade & Adedeji, ).…”
Section: Resultssupporting
confidence: 89%
“…Sparse qualitative observations indicated that abaxial cells tend to have more undulate margins than adaxial cells (Linsbauer, ; Watson, ; Arogundade & Adedeji, ). To test this across our sampling, we calculated the difference between the average adaxial solidity and the average abaxial solidity in the 146 species for which we had data from both sides of the leaf (81 eudicots, 30 monocots, 28 ferns; see the Materials and Methods section).…”
Section: Resultsmentioning
confidence: 99%
“…to have more undulations (lower solidity, Fig. 2a), in line with the qualitative literature 16,53 . The 293…”
Section: Abaxial Leaf Surfaces Present More Undulate Cells 287supporting
confidence: 90%
“…In their study, they reported that the outline of midrib and petiole and vascular bundle characteristics (number and arrangement) were important features that can delimit the genus. In the same way, Arogundade and Adedeji (2017) and Baruah et al (2017) found the foliar and petiole anatomy as a diagnostic feature in some members of the Dieffenbachia Schott (Araceae) and Smilax (Smilacaceae). Our study corroborates these previous reports.…”
Section: Tendrilmentioning
confidence: 67%